Doctoral student, Kathy Martin, in the field at La Pérouse Bay, Hudson Bay, Manitoba, Canada. - Bazely, Dawn R. (1981)
Kathy Martin in the field, with her noose-pole for catching willow ptarmigan in May 1981 in the High Willow Tundra of the Mast River, La Perouse Bay, Hudson Bay (east of Churchill, Manitoba, Canada).